The Effect Of Principal Academic Supervision And Teacher Work Motivation On The Performance Of State Elementary School Teachers - Septiani, Ranty; Ahmad, Syarwani; Firdaus, Masagus (Lembaga Bale Literasi, 2026)
This study aims, first, to analyze the effect of principals’ academic supervision on teacher performance in public elementary schools in Cluster II, Jejawi District, Ogan Komering Ilir Regency; second, to analyze the effect of teachers’ work motivation on teacher performance in public elementary schools in Cluster II, Jejawi District, Ogan Komering Ilir Regency; and third, to analyze the simultaneous effect of principals’ academic supervision and teachers’ work motivation on teacher performance in public elementary schools in Cluster II, Jejawi District, Ogan Komering Ilir Regency. The population of this study consisted of all 63 teachers in public elementary schools in Cluster II, Jejawi District, Ogan Komering Ilir Regency, all of whom were used as the research sample. Data were collected using a Likert scale–based questionnaire and analyzed using correlation and regression techniques with the assistance of the Statistical Package for the Social Sciences (SPSS) version 26, as well as manual calculations.The results show that principals’ academic supervision has an effect on teacher performance of 60.3%, while the remaining 39.7% is influenced by other variables not examined in this study. In addition, teachers’ work motivation has an effect on teacher performance of 47.5%, while the remaining 52.5% is influenced by other factors outside this study. Furthermore, principals’ academic supervision and teachers’ work motivation simultaneously have an effect on teacher performance of 86%, while the remaining 14% is influenced by other factors beyond the scope of this study.